Analisis Sistem First to File Dalam Pendaftaran Merek: Implikasi Terhadap Kasus Itikad Tidak Baik (Studi Putusan No. 3/Pdt.Sus-HKI-Merek/2024/PN Niaga Smg) - Muhammad Mufid 'Izzuddin; Septi Indrawati (Suara Edukasi Hukum, 2026)
This study aims to analyze the application of the first to file principle in trademark disputes involving elements of bad faith and to examine the judicial reasoning in Decision Number 3/Pdt.Sus-HKI-Merek/2024/PN Niaga Semarang. The Indonesian trademark law adopts a constitutive registration system that grants exclusive rights to the party who first registers the mark. Although this system ensures legal certainty, it also creates the potential for abuse through registrations made in bad faith. This research employs a normative legal method using statutory, case, and conceptual approaches. The legal materials consist of statutory regulations, court decisions, legal doctrines, and scholarly literature, which are analyzed qualitatively through systematic and argumentative interpretation. The findings demonstrate that the first to file principle remains relevant as the foundation of trademark protection; however, its application is not absolute. The court did not rely solely on formal registration status but also assessed substantive elements such as bad faith, similarity in essential elements, and prior factual use of the mark in commerce. This study proposes an integrative model that maintains the first to file system as the primary framework while incorporating elements of first to use as a corrective mechanism in assessing bad faith, thereby promoting a balance between legal certainty and substantive justice.